2D hybrid interlayer of electrochemically exfoliated graphene and Co(OH)2 nanosheet as a bi-functionalized polysulfide barrier for high-performance lithium–sulfur batteries. (20th November 2018) - Shi, Haodong; Dong, Yanfeng; Zhou, Feng; Chen, Jian; Wu, Zhong-Shuai
Abstract: Lithium sulfur (Li–S) batteries have attracted much attention because of high energy density, low cost and environmental friendliness. However, developing high-energy-density Li–S batteries is seriously hindered by their short cycling life, originating from the shuttle effect of soluble polysulfides. Herein we for the first time develop a versatile and facile strategy of assembling thin and lightweight bi-functionalized hybrid interlayer constructed by two-dimensional (2D) electrochemically exfoliated graphene and Co(OH)2 nanosheets (EG/Co(OH)2 ), positioned between the cathode and commercial polypropylene (PP) separator, for high-performance Li–S batteries with remarkably enhanced capacity, rate capability and long-term cyclability. The resulting 2D EG/Co(OH)2 hybrid interlayer features layer-stacked structure, thin thickness of 5.5 μ m, high electrical conductivity of 900 S cm −1, low mass loading of 0.20 mg cm −2, and exhibits bi-functionalized roles of polysulfide physical barrier from EG nanosheets and high chemical adsorption for polysulfides by Co(OH)2 nanosheets. As a result, the assembled Li–S batteries based on graphene-S cathode, using EG/Co(OH)2 interlayer, showed greatly enhanced discharge capacity of 918 mAh g −1 at 0.5 C, in comparison with the cells (831 mAh g −1 ) free of EG/Co(OH)2 interlayer. Furthermore, our Li–S batteries with EG/Co(OH)2 interlayer displayed outstanding rate capacity of 677 mAh g −1 at 5 C, and exceptional cycling stability with a high capacity of 565 mAh g −1 after 300 cycles at 0.5 C, corresponding to ultralow capacity fade rate of only 0.130% per cycle. Therefore, our strategy of constructing a hybrid interlayer consisting of 2D different nanosheets will offer numerous opportunities for designing long-life and high-energy-density Li–S batteries.